Records Committee review for rare bird sighting for Eskimo Curlew at Iowa before 1879 - Iowa Ornithologists' Union Records Committeeet al (1879)
Records Committee review for Eskimo Curlews at Iowa before 1879. Includes a record review document with votes, the original sighting record found in the publication Forty Years Notes of a Field Ornithologist by John Krider, and referenced by two other publications. Epson - sheet feed